2021
DOI: 10.1155/2021/5655061
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Facial Nerve Monitoring under Different Levels of Neuromuscular Blockade with Cisatracurium Besilate in Parotid Tumour Surgery

Abstract: Background. Anaesthesia can alter neuronal excitability and vascular reactivity and ultimately lead to neurovascular coupling. Precise control of the skeletal muscle relaxant doses is the key in reducing anaesthetic damage. Methods. A total of 102 patients with the normal functioning preoperative facial nerve who required parotid tumour resection were included in this study. Facial nerve monitoring was conducted intraoperatively. The surgeon stimulated the facial nerve at different myorelaxation intervals at T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
(23 reference statements)
0
6
0
Order By: Relevance
“…The development of clinical drugs used for analgesia and sedation of ICU patients has been increasing in number. Assessing the condition and determining its pharmacology can lead to better analgesia with narcotics (6)(7)(8)(9). In the ICU, we are more likely to make better treatment decisions if we understand the different effects of anesthesia on the neurovascular system (10).…”
Section: Introductionmentioning
confidence: 99%
“…The development of clinical drugs used for analgesia and sedation of ICU patients has been increasing in number. Assessing the condition and determining its pharmacology can lead to better analgesia with narcotics (6)(7)(8)(9). In the ICU, we are more likely to make better treatment decisions if we understand the different effects of anesthesia on the neurovascular system (10).…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study suggested that the increased expression of Chrna1 is an important cause of excessive sweat secretion, and the use of small molecules to block the activity of Chrna1 may be an effective method for the treatment of PFH. Cisatracurium has been reported to inhibit Chrna1, 13 and it has been used clinically as a skeletal muscle relaxant in many situations 14–16 . Therefore, we sought to investigate the effect of cisatracurium in PFH and possible mechanisms in an animal model of PFH.…”
Section: Introductionmentioning
confidence: 99%
“…Cisatracurium has been reported to inhibit Chrna1, 13 and it has been used clinically as a skeletal muscle relaxant in many situations. 14 , 15 , 16 Therefore, we sought to investigate the effect of cisatracurium in PFH and possible mechanisms in an animal model of PFH.…”
Section: Introductionmentioning
confidence: 99%
“…With the advancement in bioinformatics and highthroughput sequencing, it is now possible to screen the differentially expressed genes (DEGs) using microarray gene expression profiling (19)(20)(21)(22)(23). Publicly available databases and repositories that store information on gene expression, microarrays, and clinical samples can help understand the underlying mechanism of the disease and screen potential molecular targets quickly and efficiently before their use in clinical settings (24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%